Actual Problems of Inheritance by Will in Russia and Abroad - D. A. Melnikova (Теоретическая и прикладная юриспруденция)
This article analyzes the actual problems of inheritance by will in Russia and abroad. The problems of interpretation of the provisions of the legislation of the Russian Federation on inheritance are presented, the practical problems most often encountered in judicial practice are reflected. The development of legislation in the field of inheritance is analyzed. On the basis of the study, the authors propose measures aimed at improving the institution of  inheritance by will.